2022
DOI: 10.1177/00221465221109195
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health before and during the COVID-19 Pandemic: The Role of Partnership and Parenthood Status in Growing Disparities between Types of Families

Abstract: This study investigates mental health inequalities by family type and gender during the COVID-19 pandemic in Germany. Using data from the German Family Panel, we compared three dimensions of mental health (i.e., self-reported stress, exhaustion, and loneliness) one year before the pandemic and in spring 2020. First, two-parent families emerged as a vulnerable group, as the levels of stress and exhaustion they reported during the pandemic converged with those experienced by single parents. Second, a gender gap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 68 publications
3
11
0
Order By: Relevance
“…Our findings suggest that cognitive labor is also an important aspect of inequality in pandemic parenting. These findings further contextualize research that demonstrates negative impacts on the productivity and well‐being of female workers during the pandemic (Hiekel & Kühn, 2022; King & Frederickson, 2021; Lyttelton et al, 2020).…”
Section: Discussionsupporting
confidence: 75%
“…Our findings suggest that cognitive labor is also an important aspect of inequality in pandemic parenting. These findings further contextualize research that demonstrates negative impacts on the productivity and well‐being of female workers during the pandemic (Hiekel & Kühn, 2022; King & Frederickson, 2021; Lyttelton et al, 2020).…”
Section: Discussionsupporting
confidence: 75%
“…Using the same data as Menta (2021) , Clark and Lepinteur (2022) document that COVID-19 policy stringency produced a larger drop in women's life satisfaction, and women were found to report higher levels of general psychiatric disorders and loneliness in the UK during 2020 ( Li and Wang, 2020 ), and greater stress, lack of energy, and loneliness in Germany ( Czymara et al . 2021 , and Hiekel and Kühn, 2022 ). The ‘loneliness epidemic’ is of course not new, and was already a subject of discussion pre-COVID-19 ( Bu et al ., 2020 ; King 2018).…”
Section: Introductionmentioning
confidence: 97%
“…Scholars have found that the mental health gap that emerged between people in different types of household structures in Germany early in the pandemic was particularly large among coparents of minor children who were living together (Hiekel & Kühn, 2022). Studies investigating individual mental health and how it changed consistently found that mental health declines were steeper for mothers than for fathers, and were greater the younger the children were (Etheridge & Spantig, 2022;Hipp & Bünning, 2021;Huebener et al, 2021;Pierce et al, 2020;Vicari, Zoch, & Bächmann, 2022;Zamarro & Prados, 2021).…”
Section: Discussionmentioning
confidence: 99%